Transcatheter pulmonary valve replacement: a new polycarbonate urethane valve. (4th February 2021) - Lutter, Georg; Topal, Ayça; Hansen, Jan Hinnerk; Haneya, Assad; Santhanthan, Janarthan; Freitag-Wolf, Sandra; Frank, Derk; Puehler, Thomas
Abstract:  : OBJECTIVES: Transcatheter pulmonary valve replacement has become a valid treatment option for right ventricular outflow tract diseases. However, some limitations occur in patients with wide, compliant right ventricular outflow tracts that might be amenable to treatment with self-expanding valved protheses. An experimental ovine study was designed to evaluate a novel dip-coated, low-profile trileaflet polycarbonate urethane (PCU) heart valve mounted into a self-expandable nitinol stent. METHODS: The PCU valves were produced by a dip-coating technique, mounted in a conical-shaped nitinol stent and provided with a leaflet thickness of 100–150 µm. The valved stents were implanted percutaneously via transfemoral access in 6 consecutive sheep divided into 2 groups. Three animals were followed up for 1 month and the remainder, for 6 months. Angiographic measurements and transthoracic echocardiography were performed before and after implantation and at the end of the 1- or 6-month observation period, respectively. RESULTS: Orthotopic positioning of the valve was achieved in all animals. All except 1 had competent valves during the follow-up period. The peak-to-peak gradient across the PCU valved stents was 4.6 ± 1.0 mmHg after 1 month and 4.4 ± 2.3 mmHg after 6 months of follow-up. Macroscopic and microscopic post-mortem evaluation indicated good morphological and structural results. There were no stent fractures, leaflet calcification or thrombus formation. CONCLUSIONS: This study demonstrates successful transcatheter pulmonary valve replacement with a novel dip-coated valved nitinol stent. The trileaflet PCU prostheses indicated good functional and biocompatible properties after a 6-month observation period.